Manual Recording and Its Effect on the Effectiveness of Income Statements: A Case Study of Tour & Travel Services Companies - Alya Sabrina; Achmad Rizal (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the effect of manual financial recording systems on the effectiveness and income statements of financial management processes in tour and travel service companies. The main problem found during the research was that the financial recording process was still carried out manually using spreadsheets, which led to the risk of human error, delays in report preparation, and inaccurate records that could affect the accuracy of information for managerial decision-making, the process of fulfilling company obligations, and the company's credibility in the eyes of investors. This research was conducted using qualitative methods through direct observation and in-depth interviews with relevant parties, particularly the finance supervisor responsible for the recording process and the Chief Business Officer (CBO) who plays a role in strategic decision-making related to the direction and policy of the company's financial system. The results of the study show that the use of this manual recording system can still be used when daily transactions are not too complex or low, but when the transaction volume increases, it will have a significant impact on the accuracy and speed of presenting income statements, especially in grouping costs, recording daily transactions, and the reconciliation process. This manual financial recording system has also been proven to reduce work effectiveness because it takes longer, is prone to data duplication, and does not have an automatic validation feature. This study provides recommendations in the form of implementing a software based financial recording system to improve effectiveness, reduce the risk of errors, and support managerial decision making